Development of a climate data collector and vibration in egg conveyors in commercial households - Silva de Souza, Felipe; Mollo Neto, Mario (Seven Editora, 2023)
The egg is a food with great prominence in Brazil because of its nutritional power and low cost. With the technological advances many farms choose to automate their whole production process, however, many times these technologies may interfere and favor losses during production, requiring adjustments to avoid these losses. Therefore, it is noteworthy that problems originating from vibrations and impacts during the automated egg transportation causing cracks in eggs, besides sun exposure, are one of the main factors that stand out in the production loss of eggs. With this in mind, the present project aimed to create a hardware prototype that collects data on weather conditions and vibration of commercial aviary belts and a firmware that can be embedded in the prototype to read the information collected by the hardware and record it in a memory card for later analysis of the collected data. DOI: https://doi.org/10.56238/devopinterscie-187